Evaluation of the Anticancer and DNA-Binding Characteristics of Dichloro(diimine)zinc(II) Complexes - Bandar A. Babgi; Doaa Domyati; Magda H. Abdellattif; Mostafa A. Hussien (Chemistry, 2021)
Several metal diimine complexes have been reported to possess anticancer properties. To evaluate the anticancer properties of tetrahedral zinc(II) diimine complexes, six complexes were synthesized with the general formula M(N^N)Cl2 {where M = Zn, Pt and N^N = 2,2’-biquinoline (1), 2,2’-dipyridylketone (2) and 4-((pyridine-2-ylmethylene)amino)phenol (3)}. In general, the intrinsic DNA-binding constants for the different compounds exhibited values within close proximity; the changes in the viscosity of the CT-DNA upon binding to the compounds suggest intercalation-binding mode. Molecular docking study predicted that complexes containing the highly planar ligand 2,2’-biquinoline are capable to establish π–π interactions with nucleobases of the DNA; the other four complexes engaged in donor–acceptor interactions with DNA nucleobases. The six complexes and two reference drugs (cisplatin and sunitinib) were tested against two cancer cell lines (COLO 205 and RCC-PR) and one normal cell line (LLC-MK2), highlighting the better performance of the zinc(II) complexes compared to their platinum(II) analogues. Moreover, zinc(II) complexes have higher selectivity index values than the reference drugs, with promising anticancer properties.